Dual Gene Regulation by Hypoxia-Conditioned MSC Exosomes in a UV-B–Induced Collagen Loss Model: Targeting p21 and Cyclin D for Skin Regeneration - Riaflor Alcabedos; Ooi Siew Fong (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to investigate the effect of hypoxia-conditioned MSC-derived exosomes (E-MSCs) on the expression of p21 and Cyclin D genes in a UV-B-induced collagen loss mouse model, using in vivo experiments and gene expression analysis. Methodology: This in vivo experimental study used a Post-Test Only Control Group Design with male Wistar rats (Rattus norvegicus), UV-B lamp TLF72-100W/12 (Philips, 302 nm), RT-PCR machine (Bio-Rad CFX96), flow cytometer (BD FACSCalibur), centrifuge (Eppendorf 5804R), TFF filter (Repligen KrosFlo), Masson’s Trichrome staining, and SPSS 26.0 for data analysis. Main Findings: E-MSCs at 200 µL and 300 µL significantly increased p21 and Cyclin D gene expression in UV-B–induced collagen loss model in male Wistar rats. Highest expression was found in the 300 µL E-MSCs group. ANOVA and Kruskal–Wallis tests showed significant differences (p < 0.05) between treatment and control groups, confirming the therapeutic potential of E-MSCs in regulating gene expression related to skin regeneration. Novelty/Originality of this study: This study is the first to investigate the in vivo effects of hypoxia-conditioned MSC-derived exosomes (E-MSCs) on both p21 and Cyclin D gene expression in a UV-B–induced collagen loss model. It advances existing knowledge by revealing the dual regulatory role of E-MSCs in cell cycle arrest and proliferation, contributing to innovative skin regeneration therapies.